Power of Power To Sell as Collateral Confiscation In Debt Repayment Based on The Debt Recognition Deed - Tasia Zein, Tia; Jauhari, Iman; Rahmah, Siti (Pelopor Publikasi Akademika, 2024)
The purpose of this study is to determine the power of power to sell as collateral confiscation in debt repayment based on the debt recognition deedDeed of Debt Recognition is a deed made by a notary in the form of a Grosse Deed containing the irah-irah